Artificial Intelligence-A Note on the Present Era Deepmind-Prospects and Aspects - Sangeetha, Sangeetha (International Journal of Computer Sciences and Engineering, 2025)
An overview on the ruling technology “Artificial Intelligence” whose vision for High level-Perception has been done including its controversies. However, AI has reached its peak, the inventions like “Norman” done by MIT, which is a psychopathic robot has turned the vision or view of the entire community over AI. The AI Machines like “Cozmo” and “Moley”, who are being perfect in their purpose of creation has become an attention seeker in the views of the society. On the other hand “Deepmind” technologies explodes its perspectives and aspects towards every nook and corner of the people’s real time problems in daily life.”Alphago”, the master game being a Deepmind machine, has won the epic strong players of the game, taking AI to the top of the ladder. Notably, Deepmind technology with its amazing Neural Networks is ruling the medical society by completely changing the Lifestyle of patients. An Accurate and undoubted medicine system for everyone will be the future system which will be a dream come true for us. The future scope of AI would be a well-developed ‘AI Precision Farming’ and a strong Cyber security system which reduces the risk of Danger and a Well-developed Medicine system which will be a resolution of all the Social Problems